"A recipe for elder abuse:" From sin to risk in anti-euthanasia activism. Issue 9 (20th October 2016) - Gandsman, Ari
ABSTRACT: Anti-euthanasia activists currently make their arguments against physician-assisted dying in terms of vulnerability and risk. Tensions in this strategy emerge because many are drawn to activism out of religious beliefs. This article will explain how they have reframed their argument that physician-assisted dying is a "recipe for elder abuse." This strategy attempts to manufacture uncertainty among vulnerable groups by strategically deploying doubt against medical institutions and governments, while generating distrust among family members. This article will argue that underlying this strategic deployment of risk are beliefs that posit assisted death as polluting to society.